Mytho-auto-bio: Neil Gaiman's Sandman, the Romantics and Shakespeare's The Tempest. Issue 1 (1st July 2015) - Katsiadas, Nick
This article examines Neil Gaiman's Sandman as a series that invokes English Romanticism's perspectives of dreams, heroism, the virtue of storytelling and Shakespeare's source of authorship, bringing to the fore the series' relationship with the European literary canon. I initially discuss how popular culture reconstructs possible 'selves' of Shakespeare in ways that are designed to suit particular artistic endeavours and/or modern subjectivity, and then focus on 'how' and 'why' traditional criticism identifies an autobiographical dimension in the playwright's character Prospero, from The Tempest. Reading the character as metonymic in a Romantic vein, I construct a paradigm to shift current Sandman scholarship from the mythological level to the tropological level to examine its literary values and merit. I maintain throughout the article that Gaiman designs Morpheus with Romantic understandings of Prospero and, drawing from the larger DC Universe of superhero motifs, how Gaiman constructs Morpheus as an alter ego. Rather than a superhero, I argue that Morpheus is a Romantic hero bearing traces of the author's autobiography. After examining Gaiman's relationship with the narrative, I discuss the confluences between Gaiman and Samuel Taylor Coleridge locating Shakespeare's imaginative source in d/Dream (Morpheus) – what Coleridge names the 'Morphean Space'. Since The Tempest is believed to be Shakespeare's final play wherein he announces his exeunt from The Globe Theatre and that Gaiman intended to end Sandman with his 'The Tempest', I conclude by explaining Gaiman's use of an autobiographical simile.